Implementasi Perlindungan Hukum Terhadap Pekerja di Indonesia dalam Perjanjian Kerja Waktu Tertentu (PKWT) dan Perjanjian Kerja Waktu Tidak Tertentu (PKWTT) Menurut Undang-Undang No. 11 Tahun 2020 Tentang Cipta Kerja - Yusup Permana, Deni (Jurnal Indonesia Sosial Sains, 2022)
Efforts to create a safe haven for workers are through copyright laws. When workers' rights are running low, causing them to be far from welfare, it is necessary to play the role of copyright law, so that workers can obtain legal certainty. The purpose of this study is to obtain the implementation of legal protection aimed at the welfare of the protection of workers in a Specific Time Work Agreement (PKWT) and an Indefinite Time Worker (PKWTT) in accordance with the provisions of Law No. 11 of 2020 concerning Job Creation. Using a normative juridical approach. The results of this study indicate that in view of the frequent occurrence of violations due to unclear rules for the application of a certain time work agreement, a certain time work agreement (PKWT) has not yet achieved the desired optimal effect in its implementation. In addition, the lack of government supervision in the process of drafting work agreements with deadlines makes it easy for entrepreneurs to violate existing regulations without being subject to legal sanctions. In conclusion, the regulation regarding the Work Agreement for Certain Time and Work for Uncertain Time which is a working relationship in which the arrangement is an attempt to achieve prosperity, then the law plays a role in providing protection, security, peace and order in the association of human life.